Neuroinflammation in ALS: cause or consequence? - Van Damme, Philip (Henry Stewart Talks, 2016)
Neuropathology of amyotrophic lateral sclerosis (ALS), Neuroinflammation in human ALS, Neuroinflammation in ALS mouse model, Role of microglia in ALS, Role of T cells in ALS, TREM2, Progranulin